Relationship Between gamma-Glutamyltransferase (gamma-GT) with High Sensitive C-Reactive Protein (hs-CRP), Oxidized (Ox-LDL) and Glutathione Peroxidase (GPx) on Coronary Heart Disease (CHD) Patient - Marissa Arifin; Marsetio Donosepoetro; Sutomo Kasiman (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Recent clinical studies have suggested that γ-glutamyltransferase (γ-GT) can trigger oxidative stress within the plaque. This study aimed to investigate whether serum γ-GT might be as a risk factor of coronary heart disease (CHD), and measure the associations of serum γ-GT with high sensitive C-Reactive Protein (hs-CRP), Oxidized LDL (Ox-LDL) and Glutathione Peroxidase (GPx).METHODS: This study recruited 48 patients aged 30-70 year who underwent coronary angiography at Haji Adam Malik Medical Center at Medan between February and April 2008 and who presented at least one coronary stenosis of > 50% of the luminar diameter. The sample subjects were consecutively selected.RESULTS: γ-Glutamyltransferase was positively associated (r = 0.546) with hs-CRP as a marker of chronic inflammation after careful adjustment for other established risk factors in CHD patient. But, there was no significant difference between γ-GT in male and female patients. Further, there were no correlations between γ-GT and Ox-LDL and GPx. Ratio of γ-GT/GPx was measured as well, and it was associated with hs-CRP.CONCLUSIONS: Ratio of γ-GT/GPx was associated with inflammation process in coronary heart disease patients.KEYWORDS: γ-glutamyltransferase (γ-GT), inflammation, oxidative stress, coronary heart disease